Photoluminescence of LiF Crystals Doped with Oxygen-Containing Impurities; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Korepanov V. I. Vladimir Ivanovich; Petikar P. V. Pavel Viktorovich; Ge Guanghui (Guang Hui Ge); Lipovka A. A. Anna Anatolyevna (2018, 2018)
Title screen